Electron-flux infrared response to varying π-bond topology in charged aromatic monomers - Héctor Álvaro Galué (Nature Portfolio, 2016)
It is essential to understand the effect of molecular vibration on charge transport for better design of molecular electronics. Here, the authors test two benchmark aromatic motifs and show how the coupling between π electrons and molecular vibration is affected by molecular edge topology.